Specificities of Ethical Consent in Patients with Impairment - Abdelghaffar, Wafa; Haloui, Nadia; Bouzid, Myriam Ines; Rafrafi, Rym (Research Highlights in Disease and Health Research Vol. 2, 2023)
In modern medicine, informed consent is a moral and legal imperative. After getting sufficient information from his doctor, the patient can decide on his own treatment. Doctors may provide therapies without the patient's consent in some circumstances, such as infirmity. Some situations, however, are on the edge, like the patient described in this research who had a moderate intellectual disability and refused to get an immediate intervention for an aortic dissection. In this instance, cardiologists and psychiatrists worked together to determine whether the patient could provide his consent before deciding to respect his decision. The hospital ethics committee supported the choice to not operate on him. The paternalistic approach to the doctor-patient relationship is still common in Tunisia and other countries with similar cultural context. This essay examines ethical and legal issues while highlighting the need for universal ethical principles that apply to all patients from all backgrounds.